Increased biofilm formation ability in Klebsiella pneumoniae after short‐term exposure to a simulated microgravity environment. Issue 5 (16th May 2016) - Wang, Haili; Yan, Yanfeng; Rong, Dan; Wang, Jing; Wang, Hongduo; Liu, Zizhong; Wang, Jiaping; Yang, Ruifu; Han, Yanping
Abstract: Biofilm formation is closely related to the pathogenetic processes of Klebsiella pneumoniae, which frequently causes infections in immunocompromised individuals. The immune system of astronauts is compromised in spaceflight. Accordingly, K. pneumoniae, which used to be isolated from orbiting spacecraft and astronauts, poses potential threats to the health of astronauts and mission security. Microgravity is a key environmental cue during spaceflight. Therefore, determining its effects on bacterial biofilm formation is necessary. In this study, K. pneumoniae ATCC BAA‐1705 was exposed to a simulated microgravity (SMG) environment. K. pneumoniae grown under SMG formed thicker biofilms compared with those under normal gravity (NG) control after 2 weeks of subculture. Two indicative dyes (i.e., Congo red and calcofluor) specifically binding to cellulose fibers and/or fimbriae were utilized to reconfirm the enhanced biofilm formation ability of K. pneumoniae grown under SMG. Further analysis showed that the biofilms formed by SMG‐treated K. pneumoniae were susceptible to cellulase digestion. Yeast cells mannose‐resistant agglutination by K. pneumoniae type 3 fimbriae was more obvious in the SMG group, which suggests that cellulose production and type 3 fimbriae expression in K. pneumoniae were both enhanced under the SMG condition. Transcriptomic analysis showed that 171 genes belonging to 15 functional categories were dysregulated in this organism exposed to the SMG conditions compared with those in the NG group, where the genes responsible for the type 3 fimbriae ( mrkABCDF ) and its regulator ( mrkH ) were upregulated. Abstract : The ability of biofilm formation in Klebsiella pneumoniae was enhanced after short‐term exposure to the simulated microgravity environment. The cellulose is the major component of the biofilm produced by SMG‐treated K. pneumoniae . Those genes responsible for type 3 fimbriae (MrkABCDF) and its regulator (MrkH) are upregulated in SMG‐treated bacterial cells.